PENINGKATAN KEMAMPUAN KOGNITIF DI TAMAN KANAK-KANAK TERUNA KASIH BANGSA SANGGAU LEDO - Rotin, Rotin; Ali, Muhamad; Lestari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this research is that the teacher's learning is still monotonous. The ability to spell in children 5-6 years has not developed as expected. The form of this research is basic action using descriptive method. Based on the results of the study in general it can be concluded that: 1) Planning the learning done is categorized as